FINANCING OF HOUSING CONSTRUCTION BY COMMERCIAL BANKS THROUGH FACTOR OPERATIONS - Ziyayev Azamat Mirza ogli (Scholar Express Journals, 2025)
This article talks about the factoring instrument, which is one of the methods that commercial banks will use in the future in the process of financing housing construction. The introduction of factoring operation, similar to bank loan, in the financing of construction sphere, possible problems, achievements, character of domestic housing construction market and recommendations regarding the activity of banks as a factor are given.
Keywords: Accounts receivable; invoice; housing; financing bank